ETULay! Bridging the Learners’ Gap on Blended Learning through Nationwide Volunteer Online Tutoring Initiative - Jamisal, Mark Anthony; Núñez, Jayrome Lleva (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2022)
From March 2020 up to the present (February 2022), elementary and high schools in the Philippines have not resumed their full classroom capacity. The majority of learners are still learning from home without assurance of when they are going back to the schools. In order to augment the department’s blended program, the EdTech Unit of Information Communication Technology Services (ICTS) of the Department of Education (DepEd Philippines) has launched an online tutoring program using Facebook and YouTube to reach a larger number of learners all over the country. The program was conceived in January 2021 and has served more than two million learners in the Philippines. Using qualitative content analysis from the responses of the participants, this paper aimed at knowing the experiences of parents, this paper presents the experiences of participants in the program during the first year of its implementation. Upon the first year of its implementation, the participants were generally enthralled and positive for the initiative as it helped them ease with explaining some context that parents may not have the grasp of the information. Parents also were given springboard to talk about topics which are rather difficult to discuss with their children. Participants also highlighted that ETULay served its purpose well but hoped to be more inclusive and graphics-enhanced in the next years to come.